Innovators' vs non-innovators' perceptions of corruption in European post-transition economies - Valerija Botrić; Ljiljana Božić (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2015)
Purpose -The purpose of this paper is to analyse whether innovators perceive corruption to be systematically more important than non-innovators across different post-transition EU countries. Design/methodology/approach -We use the Business Environment Survey (BEEPS V) data. The sample consists of 3,716 firms from the post-transition EU members (Bulgaria, Romania, Latvia, Lithuania, Poland, Croatia, Slovakia, Hungary, Czech Republic, Slovenia and Estonia). We first estimate simple matching model, specifically, average treatment effect of the treated (ATT) framework. In order to explore the determinants of the innovation activity of the firms in the analysed countries, conditional on the fact that they consider the corruption to be important obstacle for their business activity, we employ the Heckman probit procedure. Findings - The results imply that there is a link between innovation activity of the firms, perceptions of corruption and the evaluation of innovation enabling specificities in the analysed countries. Research limitations/implications - Although the results confirm that in most of the analysed countries innovative firms perceive corruption to be major impediment for their business activity, based on this analysis we cannot argue that innovation activity would be higher if corruption perceptions were lower in the analysed countries. Originality/value - The results suggest that, in order to boost innovation, not only traditional innovation-supporting policy measures should be considered, but also wider spectrum of activities oriented towards business climate improvement.
Keywords: O30; D73; 330; innovation; corruption; post-transition countries